Anatomy of the March 2016 severe ozone smog episode in Mexico-City. (1st January 2021) - Osibanjo, O.O.; Rappenglück, B.; Retama, A.
Abstract: The diurnal evolution of the planetary boundary layer (PBL) is crucial to air quality studies as it impacts the exchange and distribution of pollutants close to the surface. This paper reports continuous detection of the daytime convective boundary layer height, the stable boundary layer height, and the residual layer height as estimated from the vertical profiles of virtual potential temperature, and moisture retrieved from a microwave radiometer (MWR) in Mexico City for the period 6–18 March 2016. This period included a severe smog episode. We analyzed the anatomy of this episode utilizing continuous air quality measurements recently deployed at elevated locations surrounding the basin of Mexico City, which were used to determine the impact of the background or residual pollutants during the severe smog episode in combination with back trajectory analysis and radar wind profiles data to track transport processes within the Mexico City basin. The first few days prior to the smog episode were impacted by the passage of a deep upper tropospheric trough and strong advection. Shortly before the smog episode, daytime maximum PBL height still reached ~2.5 km above ground level but then dropped to ~1.2–1.7 km above ground level for the most severe pollution days. During the first days with strong advection, the pollutant concentrations were flushed out from the basin and/or could not accumulate (maximum hourly ozone and carbon monoxide mixing ratios of ~50 ppbv and ~0.5 ppmv, respectively). At the departure of the storm, the winds became weaker, and a strong near surface temperature inversion was observed at nighttime increasing the nighttime mixing ratio of carbon monoxide to ~2.5 ppmv and daytime ozone mixing ratio to ~200 ppbv, which resulted in one of the most severe smog episodes in Mexico City over the last decade. Our results point to strong photochemical processes confined to the PBL within the Mexico City basin, whose maximum daytime convective boundary layer heights hardly surpassed the surrounding average mountain top heights. Highlights: Boundary layer (BL) evolution observations during O3 smog episode in Mexico City. Preceding cold front reduces near surface θv suppressing BL growth. First time, high altitude stations included representing residual layer conditions. Recirculation within the BL critically impacts air quality in Mexico City. Strong photochemical processes confined to the BL within the Mexico City basin.